Kandungan Lisin dan Pertumbuhan Ikan Gabus (Channa striata) yang Diberi Pakan Berbeda - Warisan Warisan; Ade Dwi sasanti; Yulisman Yulisman (Seminar Nasional Lahan Suboptimal, 2018)
Warisan et al, 2019.The Content of Lysine and Growth of Snakehead Fish (Channa striata) Fed by Different Feed. pp. 384-393. Essential amino acids are amino acids that cannot be synthesized by the body so that they require outside intake. One of the essential amino acids in snakehead fish is lysine. Lysine plays a role in the process of antibody formation, blood circulation and growth. The feed given to snakehead fish that is cultivated also determines the content of snakehead lysine. The purpose of this study was to determine the content of lysine and the growth of snakehead fish fed differently. The study was conducted from May to July 2018 at Laboratorium Kolam Percobaan, Faculty of Agriculture and Laboratorium Bioproses, Faculty of Engineering of Sriwijaya University. The study was designed using a completely randomized design with three treatments, each repeated four times. The Treatments are the different types of feed given, P1 fish were given commercial feed with 32% protein; P2 fish is given commercial feed with 32% protein and 3.5% black cumin added; P3 fish are fed with fresh water and sea water fish flesh in a ratio of 1: 1. Fish cultured is carried out for 30 days in hapa in a concrete pond. Density of fish is 2 fish per liter. Fish are fed at satiation with a frequency of three times a day. The snakehead fish treated with freshwater and marine trash fish produced the highest increase in lysine content, which was 0.060 mg / ml while P1 was 0.024 mg / ml and P2 0.031 mg / ml. The absolute growth of snakehead fish in each treatment was P1 1.34 cm; P2 1.24 cm; P3 is 1.93 cm and absolute weight growth is P1 2.31 g; P2 2.17 g; P3 3.58 g. The results showed that different types of feed were not significantly affected the levels of snakehead fish lysine but significantly affected the growth of snakehead fish.